2021
DOI: 10.1016/j.atherosclerosis.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Association between geriatric nutritional risk index and stroke risk in hemodialysis patients: 10-Years outcome of the Q-Cohort study

Abstract: The geriatric nutritional risk index (GNRI), which is calculated using the serum albumin level and body mass index, is a nutritional marker associated with an increased risk of cardiovascular events in patients who are receiving hemodialysis. However, no studies have examined the association between the GNRI level and the incidence of stroke in this population. Methods: Three thousand forty-five patients were registered in the Q-Cohort Study, which is a multicenter, observational cohort of hemodialysis patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
18
1
Order By: Relevance
“…Because of its objective nature, GNRI overcomes the problems of traditional nutrition indicators, including subjective issues such as mini-nutritional assessments ( 29 ). And GNRI correlates well with malnutrition-inflammation scores and has been regarded as one of the gold standards for nutritional assessment of elderly patients with chronic diseases ( 10 , 30 ). There is evidence that patients with chronic illnesses, including chronic hemodialysis and peripheral vascular disease, have a lower GNRI ( 31 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its objective nature, GNRI overcomes the problems of traditional nutrition indicators, including subjective issues such as mini-nutritional assessments ( 29 ). And GNRI correlates well with malnutrition-inflammation scores and has been regarded as one of the gold standards for nutritional assessment of elderly patients with chronic diseases ( 10 , 30 ). There is evidence that patients with chronic illnesses, including chronic hemodialysis and peripheral vascular disease, have a lower GNRI ( 31 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The geriatric nutritional risk index (GNRI) is a simple, well-established nutrition assessment tool that uses serum albumin and body mass index (BMI) ( 9 ). Recent studies have shown that GNRI is associated with the development of atherosclerosis and an increased risk of cardiovascular mortality in older patients ( 10 , 11 ). However, studies on GNRI as a predictor of new-onset stroke are still limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has shown that GNRI is a good surrogate marker of nutritional status, and that GNRI is a predictor of comorbidities and mortality in patients receiving hemodialysis or peritoneal dialysis [9–13]. A recent meta‐analysis pooled data for 10 739 patients from 19 cohort studies published between 2010 and 2018 [17].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Yamada et al [9] introduced the clinical usefulness of the GNRI in patients receiving hemodialysis as a simple tool for assessing nutritional status. Mounting evidence has shown that a lower GNRI value is closely associated with an increased risk of morbidity and mortality in patients receiving hemodialysis [10][11][12]. However, the GNRI calculation formula is a bit cumbersome and requires calculators.…”
Section: Introductionmentioning
confidence: 99%